IMPLEMENTASI ANALISIS SWOT DALAM STRATEGI PENGEMBANGAN FESTIVAL FILM SOLO DOCUMENTARY - Dimas Erdhinta Pratama Putra; Anggra Agastyassa Owie (Institut Seni Budaya Indonesia Bandung, 2023)
ABSTRACT This research aims to analyze internal and external factors in the management of the Solo Documentary Film Festival and develop appropriate development strategies for the management and poverty of the Solo Documentary Film Festival. The location of this research is Surakarta City, Central Java Province. The research uses qualitative methods. The data analysis technique uses SWOT analysis by processing Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE). This research aims to formulate a strategy for developing the Solo Documentary film festival. The internal factors for managing the Solo Documentary Film Festival are a wide communication and friendship network, competence in managing a documentary film festival, consistency in achieving goals and carrying out established work programs. Meanwhile, external factors that can support the success of the Solo Documentary Film Festival are the stronger support from the people of Surakarta for the documentary film festival and increasingly improving technology that can support performance. Based on the EFE matrix and IFE matrix tables, the total EFE score is 3.2506 and the total IFE score is 2.8337, which places the Solo Documentary Film Festival in cell II position, namely Growth and Build. ABSTRAK Penelitian ini bertujuan untuk menganalisis faktor internal dan faktor eksternal pengelolaan Festival Film Solo Documentary serta merumuskan strategi pengembangan yang tepat untuk pengelolaan dan keberlanjutan Festival Film Solo Documentary. Lokasi penelitian ini di Kota Surakarta, Provinsi Jawa Tengah. Penelitian menggunakan metode kualitatif. Teknik analisis data dengan menggunakan analisis SWOT dengan mengolah Internal Factor Evaluation (IFE) dan External Factor Evaluation (EFE). Penelitian ini bertujuan untuk merumuskan formulasi strategi pengembangan festival film Solo Documentary. Faktor internal pengelolaan Festival Film Solo Documentary adalah jaringan komunikasi dan pertemanan luas, kompetensi dalam pengelolaan festival film dokumenter, konsisten mencapai tujuan dan jalankan program kerja yang ditetapkan. Sedangkan faktor eksternal yang dapat menunjang keberhasilan Festival Film Solo Documentary adalah adanya dukungan masyarakat Surakarta semakin kuat terhadap festival film dokumenter dan semakin baiknya teknologi yang mampu menunjang kinerja. Berdasarkan tabel matrik EFE dan matrik IFE diperoleh hasil total skor EFE 3.2506 dan total skor IFE 2.8337 yang menempatkan Festival Film Solo Documentary di posisi sel II yakni Growth and Build .